Conformation and recognition of DNA modified by a new antitumor dinuclear PtII complex resistant to decomposition by sulfur nucleophiles - Zerzankova, Lenka; Suchankova, Tereza; Vrana, Oldrich; Farrell, Nicholas P; Brabec, Viktor; Kasparkova, Jana (Biochemical pharmacology, 2010)
Reported herein is a detailed biochemical and molecular biophysics study of the molecular mechanism of action of antitumor dinuclear Pt(II) complex [{PtCl(DACH)}(2)-mu-Y](4+) [DACH=1,2-diaminocyclohexane, Y=H(2)N(CH(2))(6)NH(2)(CH(2))(2)NH(2)(CH(2))(6)NH(2)] (complex 1). This new, long-chain bifunctional dinuclear Pt(II) complex is resistant to metabolic decomposition by sulfur-containing nucleophiles. The results show that DNA adducts of 1 can largely escape repair and yet inhibit very effectively transcription so that they should persist longer than those of conventional cisplatin. Hence, they could trigger a number of downstream cellular effects different from those triggered in cancer cells by DNA adducts of cisplatin. This might lead to the therapeutic effects that could radically improve chemotherapy by platinum complexes. In addition, the findings of the present work make new insights into mechanisms associated with antitumor effects of dinuclear/trinuclear Pt(II) complexes possible.
Keywords: sekvence nukleotidů; Nucleic Acid Conformation; protinádorové látky; molekulární sekvence - údaje; Organoplatinum Compounds; Sulfur; Fluorescence; DNA Repair; glutathion; oprava DNA; bezbuněčný systém; konformace nukleové kyseliny; DNA; Glutathione; Molecular Sequence Data; Base Sequence; Cell-Free System; organoplatinové sloučeniny; síra; fluorescence; Antineoplastic Agents